HUBUNGAN PENGETAHUAN IBU TENTANG MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) DENGAN MOTIVASI MEMBERIKAN MP-ASI TEPAT WAKTU - Liza Wati; Nur Afrinis Afrinis; Erlinawati Erlinawati (Jurnal Doppler, 2021)
Complementary feeding of breastmilk to infants less than 6 months of age has an impact on digestive disorders, allergies, and growth disorders. Mother's knowledge about complementary foods affects the timing of complementary feeding. This study aims to determine the relationship between maternal knowledge and motivation to provide MP-ASI on time in Rimba Melintang Village, Rokan Hilir Regency in 2020. This type of research is quantitative with a cross sectional approach. The population of this research were 95 mothers who have infants 0-6 months in Rimba Melintang Village with total sampling technique. The study was conducted in October - November 2020. The data collection technique used a questionnaire. The data analysis used was univariate and bivariate analysis with the chi-square test. The results showed that respondents' insufficient knowledge of complementary foods (62.1%) and respondents were not motivated to provide complementary breastfeeding on time (60%). There was a relationship between maternal knowledge and motivation to provide complementary breastfeeding on time with a value of p = 0.028. The conclusion was the lack of motivation of mothers in providing complementary breastfeeding on time because of low parental knowledge. It was recommended that health workers be more active in providing education about complementary foods and the importance of exclusive breastfeeding for infants.